2013
DOI: 10.1159/000356591
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses TPA-Induced Fibronectin Expression through the Inhibition of VEGF Secretion in Breast Cancer Cells

Abstract: Background/Aims: Berberine (BBR) is an isoquinoline alkaloid and is beneficial for the anticancer effect on a variety of human tumor cells. However, BBR's anti-angiogenesis property and its clinical potential as an inhibitor of tumor angiogenesis in breast cancer cells have not been fully elucidated. Here, we investigated the effect of BBR on TPA-induced VEGF and fibronectin (FN) as well as VEGF-induced FN in breast cancer cells. Methods: The secretion of VEGF protein was detected by ELISA. Fibronectin mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…On the other hand, chemotherapy is commonly applied for inoperable HCC, but its results are often discouraging because of chemoresistance conferred by p53 mutation in HCC cells and toxicity of chemotherapeutic agents to normal cells [28]. The potent anti-tumor effects of berberine has been reported in multiple cancer types [2,6,8,9]. In agreement with other published reports showing the anti-cancer effects of berberine, we have also demonstrated the inhibitory effects of berberine on the growth of HCC in vivo (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, chemotherapy is commonly applied for inoperable HCC, but its results are often discouraging because of chemoresistance conferred by p53 mutation in HCC cells and toxicity of chemotherapeutic agents to normal cells [28]. The potent anti-tumor effects of berberine has been reported in multiple cancer types [2,6,8,9]. In agreement with other published reports showing the anti-cancer effects of berberine, we have also demonstrated the inhibitory effects of berberine on the growth of HCC in vivo (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Coptis Rhizome has been used for centuries by Chinese medicine physician for the treatment of cancer and inflammatory diseases [2]. Berberine is known to possess potent anti-cancer activity in several cancer models including, breast, gastric and colon cancers, nasopharyngeal carcinoma (NPC) as well as HCC [3][4][5][6][7][8]. The anti-tumor activity of berberine includes the induction of cancer cell apoptosis through affecting the normal mitochondria functioning [5,8], anti-angiogenesis by destabilizing of HIF-1α protein in hypoxic gastric adenocarinoma cells [7], and suppressing of VEGF secretion in breast and gastric cancer cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, low-dose treatment (≤ 20 mM) with BBR induces G1/S arrest, while high-dose treatment (50 mM) with BBR inhibits the G2/M checkpoint in RM-1 prostate cancer cells [32]. BBR also inhibits tumor cell invasion and angiogenesis, which in turn suppresses cancer metastasis, by suppression of MMP-2, MMP-9, and VEGF [23, 33, 34]. Consistent with previous studies, we show that BBR induces arrest in the G0/G1 phase and inhibits anchorage-independent growth in MDA-MB231 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin-binding EGF-like growth factor (HB-EGF) is an intermediate molecule for TGF-β-mediated EGFR transactivation, which subsequently triggers the transcriptional activity of FN via activation of ERK and p38MAPK in glomerular mesangial cells [27]. Moreover, vascular endothelial growth factor (VEGF) also augments FN expression in breast cancer cells via the PI-3K/Akt-dependent pathway [29]. In the present study, we found that induction of FN by HER2 activation decreased in response to treatment with UO126 (a MEK 1/2 inhibitor), LY294002 (a PI-3K inhibitor), and Stattic (a STAT3 inhibitor), in SKBR3 cells.…”
Section: Discussionmentioning
confidence: 99%